The Influence of Vanadium Additions on Isothermally Formed Bainite Microstructures in Medium Carbon Steels Containing Retained Austenite - Irina Pushkareva (Metals, 2020)
The influence of V additions on isothermally formed bainite in medium carbon steels containing retained austenite has been investigated using in-situ high energy X-ray diffraction (HEXRD) and ex-situ electron energy loss spectroscopy (EELS) and energy dispersive X-ray analysis (EDX) techniques in the transmission electron microscope (TEM). No significant impact of V in solid solution on the bainite transformation rate, final phase fractions or on the width of bainite laths was seen for transformations in the range 375−430 °C. No strong influence on the dislocation density could be detected, although quantitative analysis was impeded by ferrite tetragonality. A reduction in the carbon content of retained austenite Cγ that is not believed to be due to competition with VC or cementite precipitation was observed. No influence of V on the carbon supersaturation in bainitic ferrite Cb could be directly measured, although carbon mass balance calculations suggest Cb slightly increases. A beneficial refinement of blocky MA and a corresponding size effect induced enhancement in austenite stability were found at the lowest transformation temperature. Overall, V additions result in a slight increase in strength levels.